The impact of a positive discipline group intervention on parenting self-efficacy among mothers of young children - Liu, Jian; Liu, Xiaojuan; Ding, Meifang (Frontiers in Public Health, 2024)
Introduction: Instilling healthy behaviors in early childhood is crucial as they can have lifelong impacts. However, many Chinese mothers lack effective parenting strategies, resulting in low self-efficacy. Positive Discipline, a non-punitive and non-indulgent approach, can help enhance maternal parenting self-efficacy and promote healthy lifestyle behaviors in children. This study explores the impact of a Positive Discipline group intervention on the parenting self-efficacy of Chinese mothers and how it can contribute to promoting diet and healthy lifestyle behaviors in early childhood.We randomly selected 70 mothers with low parenting self-efficacy from a kindergarten in China, dividing them into an intervention group (35 participants) and a control group (35 participants). The intervention group received a 6-week Positive Discipline intervention, while the control group received no intervention. The intervention aimed at helping mothers nurture their children in a kind and firm manner. We used paired samples t-tests and independent samples t-tests to compare changes in parenting self-efficacy scores before and after the intervention.Results: Results showed that the intervention group's parenting self-efficacy scores significantly improved after the intervention, from an average score of 25.00±4.08 to 36.29±2.99 (p<0.05, Cohen's d=3.156). Significant improvements were observed in areas like "believing their parenting style benefits their child's growth" and "knowing how to effectively parent their children." The control group's average scores showed no significant changes between pre-and post-intervention (pre: 25.07±5.33; post: 24.86±5.75, p>0.05, Cohen's d=0.076). Furthermore, three months post-intervention, the intervention group's scores remained significantly higher than pre-intervention (p<0.05), demonstrating the intervention's lasting effect.This study demonstrates that the Positive Discipline group intervention significantly enhances parenting self-efficacy in Chinese mothers, promoting healthy lifestyle behaviors in early childhood. Providing continuous support and guidance to mothers can help solidify their parenting confidence, ensuring long-term intervention success. Future research should explore how group interventions can effectively integrate healthy behaviors into early childhood routines and impact children's diet and lifestyle behaviors.